2013
DOI: 10.1111/febs.12131
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of recombinant Ca2+ATPase studied by reaction‐induced infrared difference spectroscopy

Abstract: Recombinant Ca2+ -ATPase was expressed in Saccharomyces cerevisiae with a biotin-acceptor domain linked to its C-terminus by a thrombin cleavage site. We obtained 200 lg of~70% pure recombinant sarcoendoplasmic reticulum Ca 2+ -ATPase isoform 1a (SERCA1a) from a 6-L yeast culture. The catalytic cycle of SERCA1a was followed in real time using rapid scan FTIR spectroscopy. Different intermediate states (Ca 2 E1P and Ca 2 E2P) of the recombinant protein were accumulated using different buffer compositions. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 45 publications
0
18
1
Order By: Relevance
“…We utilized quantitative immunoblotting and Coomassie densitometry to compare the relative amount of SERCA protein in SR vesicles from horse versus rabbit muscle. For standardization, the SERCA content of SR vesicles from rabbit fast-twitch (white) muscle has been determined to be 55-70% of total protein (weight/weight), i.e., 5.0-6.4 nmol SERCA/mg rabbit SR protein (98,(100)(101)(102). Immunoblotting with anti-SERCA1 mAb VE12 1 G9 demonstrated that SR vesicles from horse gluteal muscle express ~35% the relative amount of SERCA1 as compared to rabbit SR (Figure 5A, Figure S5), although this is probably a slight underestimate of total SERCA content, since horse SR (10KP) also expresses a small amount of ATP2A2 (SERCA2) (Figure 1), which is incompatible with the use of anti-SERCA1 mAb VE12 1 G9.…”
Section: An Improved Fractionation Protocol Increases the Purity Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized quantitative immunoblotting and Coomassie densitometry to compare the relative amount of SERCA protein in SR vesicles from horse versus rabbit muscle. For standardization, the SERCA content of SR vesicles from rabbit fast-twitch (white) muscle has been determined to be 55-70% of total protein (weight/weight), i.e., 5.0-6.4 nmol SERCA/mg rabbit SR protein (98,(100)(101)(102). Immunoblotting with anti-SERCA1 mAb VE12 1 G9 demonstrated that SR vesicles from horse gluteal muscle express ~35% the relative amount of SERCA1 as compared to rabbit SR (Figure 5A, Figure S5), although this is probably a slight underestimate of total SERCA content, since horse SR (10KP) also expresses a small amount of ATP2A2 (SERCA2) (Figure 1), which is incompatible with the use of anti-SERCA1 mAb VE12 1 G9.…”
Section: An Improved Fractionation Protocol Increases the Purity Of Smentioning
confidence: 99%
“…Semi-quantitative immunoblot analysis of four horse SR preps using pAb GS3379 and a synthetic horse SLN standard determined that native SLN is expressed at 0.16 ± 0.015 nmol SLN/mg SR protein (Figure S6). The expression level of SERCA in horse SR is estimated at 2.7 nmol SERCA/mg SR protein (see above), per content assessed by Coomassie densitometry (Figure S4) and SERCA immunoblotting (Figure 5, Figure S5) using rabbit SR as a relative SERCA standard, with 5.0-6.4 nmol SERCA/mg SR protein (98,100,101). Thus, quantitative immunoblotting using the anti-horse-SLN pAb 3379 and a synthetic horse SLN peptide standard determined that SR vesicles from horse gluteal muscle express a minor ratio of 0.059 ± 0.005 SLN/SERCA (mol/mol protein).…”
Section: Horse Gluteal Muscle Expresses a Minor Level Of Sln Protein mentioning
confidence: 99%
“…In the case of membrane proteins and photoactive proteins, a variety of systems have been investigated using the approaches described in this review and first introduced for bacteriorhodopsin. A few examples are the photosystem II [116,152], photoactive yellow protein (PYP) [59,118,124,246]; Ca 2+ -ATPase [21,22,52,98,133]; green fluorescent protein (GFP) and potassium channels [92,230]. One measure of the growth of FTIR difference spectroscopy of biomolecules is shown in Fig.…”
Section: Beyond Bacteriorhodopsinmentioning
confidence: 99%
“…Thus, while a few members of the P‐type ATPase family occur at high enough concentration in the membrane to allow characterization by triggering in the native environment, the vast majority would have to be expressed from recombinant sources. For the P‐type ATPases, only the Ca 2+ ATPase transporter has been characterized in a purified form of the full‐length protein from a recombinant source using FTIR spectroscopy . Therefore, optimization of triggering conditions in non‐native environments aimed at proteins from recombinant sources will significantly increase the number of targets for time‐resolved studies.…”
Section: Introductionmentioning
confidence: 99%
“…For the P-type ATPases, only the Ca 21 ATPase transporter has been characterized in a purified form of the full-length protein from a recombinant source using FTIR spectroscopy. [28] Therefore, optimization of triggering conditions in non-native environments aimed at proteins from recombinant sources will significantly increase the number of targets for time-resolved studies. In a first effort to track the reaction of Type-I ATPases, hydrolysis of ATP was monitored for a Cu 1 ATPase construct containing only the soluble nucleotide-binding and phosphorylation domains using timeresolved FTIR spectroscopy.…”
mentioning
confidence: 99%